4x-y-5z=1 x+y-2z=6 3x-2y-6z=2 решить методом крамера

Maksimir909 Maksimir909    2   26.05.2019 00:00    0

Ответы
Love25252525 Love25252525  22.06.2020 08:01
4-1-5=1
1+1-2=6
3-2-6=2
▲ =  \left[\begin{array}{ccc}4&1&5\\1&1&2\\3&2&6\end{array}\right] = 24+10 - 6 - 15 - 16 - 6= 3

▲1 = \left[\begin{array}{ccc}1&1&5\\6&1&2\\2&2&6\end{array}\right] = 6 + 60 + 4 -10 - 4 - 36 = 20

▲2 = \left[\begin{array}{ccc}4&1&5\\1&6&2\\3&2&6\end{array}\right] = 144 + 10 + 6 - 90 - 16 - 6 = 48

▲3 = \left[\begin{array}{ccc}4&1&1\\1&1&6\\3&2&2\end{array}\right] = 8 + 2 + 18 - 3 - 48 - 2 = -25

x1=\frac{▲1}{▲}\frac{20}{3} = 6.6

x2=\frac{▲2}{▲} = \frac{48}{3} = 16

x3=\frac{▲3}{▲} = \frac{-25}{3} = 8.3

 ответ:(6.6;16;8.3).
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра